Evaluation of fecundity, fertilization, hatching, and gonadosomatic index of exotic clarias gariepinus (Burchell, 1822) and native clarias macromystax (Gunther, 1864) under semi-arid conditions of Nigeria - Esa, Yuzine B.; Dadile, Abdulrahman Muhammad; Syukri, Fadhil; Christianus, Annie; Diyaware, Mohammad Y. (Multidisciplinary Digital Publishing Institute, 2023)
The study evaluates the hybridizations between two African catfish, C. gariepinus and C. macromystax, using artificial reproduction. Fecundity and gonadosomatic index were assessed, and growth performance at different developmental stages was evaluated. The results indicated that both species possess a similar gonadosomatic index. The parent C. gariepinus possesses significantly (p < 0.05) higher male reproductive quality than C. macromystax. Fecundity was significantly higher (p < 0.05) in the female parent of C. macromystax and lower in C. gariepinus. The highest fertilization rates and hatching rates were achieved in the hybrid cross of ♀C. macromystax × ♂C. gariepinus (♀Cm × ♂Cg) which also recorded the lowest deformed larva rate. Survival rates at the larval stage were more than 80%, with the highest record of survival in the hybrid ♀Cm × ♂Cg. However, survival rates in the fry stage were lower than 70%. The hybrid cross (C. macromystax × C. gariepinus) outperformed the parental cross of C. macromystax but was not significantly similar to the parental cross of C. gariepinus. The study revealed the potential of the hybrid ♀C. macromystax × ♂C. gariepinus, and hybridizations of ♀C. macromystax × ♂C. gariepinus (♀Cm × ♂Cg) are indeed possible and proved to have a better growth and survival rate under semi-arid conditions, which would contribute significantly to the improvement of C. macromystax production in captivity.